2020
DOI: 10.1097/bpo.0000000000001556
|View full text |Cite
|
Sign up to set email alerts
|

Use of PROMIS in Assessment of Children With Ponseti-treated Idiopathic Clubfoot: Better Scores With Greater Than 3 Years of Brace Use

Abstract: Background: Patient-Reported Outcomes Measurement Information System (PROMIS) is a well-validated tool used to measure health-related quality of life for children and adolescents with chronic medical conditions. The current study evaluates PROMIS scores in 3 domains for children with Ponseti-treated idiopathic clubfoot. Methods: This is a retrospective cohort study of 77 children, ages 5 to 16 years, treated by Ponseti protocol for idiopathic clubfoot. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 30 publications
2
14
0
Order By: Relevance
“…Aulie et al3 found that 96% of school aged children treated for idiopathic clubfoot with the Ponseti method have normal function when compared with age-matched controls in the same population. Several other studies similarly demonstrated comparable activity levels and have similar patient reported outcome scores when compared with the general pediatric population 4–6. For patients diagnosed in utero, Mahan et al7 found that prenatal counseling of families by an orthopaedic surgeon did not decrease parental anxiety; however, anxiety decreased as treatment progressed.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Aulie et al3 found that 96% of school aged children treated for idiopathic clubfoot with the Ponseti method have normal function when compared with age-matched controls in the same population. Several other studies similarly demonstrated comparable activity levels and have similar patient reported outcome scores when compared with the general pediatric population 4–6. For patients diagnosed in utero, Mahan et al7 found that prenatal counseling of families by an orthopaedic surgeon did not decrease parental anxiety; however, anxiety decreased as treatment progressed.…”
Section: Resultsmentioning
confidence: 91%
“…Several other studies similarly demonstrated comparable activity levels and have similar patient reported outcome scores when compared with the general pediatric population. [4][5][6] For patients diagnosed in utero, Mahan et al 7 found that prenatal counseling of families by an orthopaedic surgeon did not decrease parental anxiety; however, anxiety decreased as treatment progressed.…”
Section: Clubfootmentioning
confidence: 99%
“…14 The MCID is reported to be 2 to 3 points for pain and mobility and 3 points for peer relationships. [15][16][17][18][19] Utilizing PROMIS data from children with ITW may be beneficial in understanding the patient perspective and priorities regarding this diagnosis. Our null hypothesis is that PROMIS metrics in children with ITW do not differ significantly from those of healthy children.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with previous studies, we defined recurrence of talonavicular deformity as lateral TAMBA measuring >30 degrees in a previously corrected foot and radiographic pes valgus as an AP talocalcaneal angle >40 degrees [20,23]. Additionally, all patients who were seen after 2015 completed questionnaires on the pain interference and peer relationship domains of the Patient-Reported Outcomes Measurement Information System (PROMIS) platform as several past studies have highlighted the advantages of using this technology [28–31]. This information system uses a score of 50 points to represent a reference population and 10 points represents one SD from the reference population.…”
Section: Methodsmentioning
confidence: 95%